Texture of materials of elements of tribological systems of machines and mechanisms in non-equilibrium processing and functioning conditions - Aulin, V.V.; Manko, Ye.V.; Chumak, V.M.; Lysenko, S.V.; Derkach, O.D.; Makarenko, D.O. (Problems of Tribology, 2025)
The article is devoted to microtexturing of metal and polymer materials of tribological system elements, its influence on the characteristics and properties of working surfaces of samples and parts. Various types of microtexture of steel and composite materials based on zirconium oxide are considered. The mechanism of their formation is clarified. Mainly, the mechanisms of microtexturing are associated with the field of tension created during friction and laser processing. It is determined that laser processing of steel samples leads to combined microtexturing and a texture gradient along the depth of the surface layer of the sample. Texture in composites is revealed both during laser processing and during friction testing. It is shown that the revealed texture positively affects the operational characteristics of parts, increasing the level of reliability and wear resistance, as well as the tribological efficiency of tribocouplings of parts of assemblies, systems, units of machines and mechanisms